Development and characterization of embelin-loaded nanolipid carriers for brain targeting. (3rd April 2017) - Sharma, Nancy; Bhandari, Saurav; Deshmukh, Rahul; Yadav, Awesh K; Mishra, Neeraj
Abstract: The objective of present work was to enquire the potential use of embelin-loaded nanolipid carriers for brain targeting. The average particle size and polydispersity index (PDI) of optimized formulation (F19) were found to be 152 ± 19.7 nm and 0.143 ± 0.023, respectively. Nanolipid carrier (NLC) was also significantly attenuated pentylenetetrazole (PTZ)-induced biochemical parameters in comparison to plain embelin that results in an increase in the level of malondialdehyde (MDA), nitrite, and reduction in the level of glutathione. From the results, it was concluded that embelin-NLCs developed as a beneficial carrier to achieve sustained release and brain targeting through nasal route.